On subordination for certain subclass of analytic functions - Liu Jinlin (International Journal of Mathematics and Mathematical Sciences)
In the present paper the class Pn[α,M] consisting of functions f(z)=z+∑k=n+1∞akzz(n≥1), which are analytic in the unit disc E={z:|z|<1} and satisfy the condition |f′(z)+αzf″(z)−1|<M is introduced. By using the method of differential subordination the properties of the class Pα[α,M] are discussed.